Social support status of the elderly population in selected villages in a central India district - Ruchita R Khandre; Abhishek Raut; Anuj Mundra (Indian Journal of Community Medicine, 2023)
Background: Social support has been considered an important social determinant of health because it assists individuals in reaching their physical and emotional needs. The current study was proposed to assess the social support status of the elderly in rural central India. Material and Methods: This observational cross-sectional study was conducted in selected four villages in central India on 460 elderly individuals for 5 months (Aug-Dec 2021) with the use of the MSPSS (Multi-dimensional Scale Perceived Social Support) questionnaire. Univariate analysis and multivariate analysis were carried out using R software. Result: Out of 460, 37 (8.04%) of the elderly were found to have low, 177 (38.47%) were moderate, and 246 (53.48%) were having high social support. The result showed age and education of the elderly were significantly associated with social support. Conclusion: Intergenerational activities, provision and strengthening of social platforms, and the addition social support components with comprehensive geriatric assessment can improve the current status.